Tracking control of uncertain surface vessels with global finite-time convergence - Van, Mien (2023)
This paper investigates an innovative control technique for uncertain surface vessels working in enhanced sea states to guarantee global finite-time convergence. First, a new finite-time backstepping approach is investigated. However, the effects of the uncertainties and disturbances reduce the closed-loop performance and prevent the global finite-time convergence of the system. In order to estimate these effects, an innovative finite-time disturbance observer is taken into consideration. The combination between the finite-time backstepping approach and the finite-time disturbance estimation creates a control system providing finite-time convergence of the system. The proposed approach is then tested on a tracking control problem for a surface vessel. The simulation results unveil the innovation of the proposed approach compared with existing ones.